1997
DOI: 10.1074/jbc.272.23.14921
|View full text |Cite
|
Sign up to set email alerts
|

5-Azadeoxycytidine-induced Chromatin Remodeling of the Inactive X-linked HPRT Gene Promoter Occurs prior to Transcription Factor Binding and Gene Reactivation

Abstract: During the process of 5-aza-2-deoxycytidine (5aCdr)-induced reactivation of the X-linked human hypoxanthine phosphoribosyltransferase (HPRT) gene on the inactive X chromosome, acquisition of a nucleasesensitive chromatin conformation in the 5 region occurs before the appearance of HPRT mRNA. In vivo footprinting experiments reported here show that the 5aCdr-induced change in HPRT chromatin structure precedes the appearance of three footprints in the immediate 5 flanking region that are characteristic of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Because differential DNA methylation of the active and inactive HPRT promoters is a prominent feature of the HPRT locus and because demethylation of the promoter by 5aCdr is closely associated with the remodeling of chromatin in the promoter region (27,44), it was conceivable that DNA methylation could play a role in establishing and/or maintaining the differential nucleosomal architecture of the active and inactive HPRT promoter regions. However, our analysis of in vitro chromatin assembly on methylated and unmethylated HPRT promoter templates (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because differential DNA methylation of the active and inactive HPRT promoters is a prominent feature of the HPRT locus and because demethylation of the promoter by 5aCdr is closely associated with the remodeling of chromatin in the promoter region (27,44), it was conceivable that DNA methylation could play a role in establishing and/or maintaining the differential nucleosomal architecture of the active and inactive HPRT promoter regions. However, our analysis of in vitro chromatin assembly on methylated and unmethylated HPRT promoter templates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Litt et al (27) have shown that, during the course of HPRT gene reactivation on the inactive X chromosome by 5aCdr, chromatin remodeling of the promoter region from a nuclease-resistant to a nuclease-accessible conformation occurs prior to both transcription factor binding and the appearance of mRNA. Presumably, the 5aCdr-induced remodeling of the promoter region consists of converting the nucleosomal organization on the inactive promoter, where nucleosomes are not translationally positioned across the promoter region but rather are rotationally positioned over key regulatory regions, to a transcriptionally competent structure that contains translationally positioned nucleosomal arrays flanking a nucleosome-free region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a number of genes, formation of promoter DNase I HS sites precedes active transcription [50][51][52], perhaps reflecting the activity of chromatin remodeling complexes. Indeed, maintenance of expression from the MoMuLV LTR requires Bramha, the catalytic subunit of one of the mammalian SWI/SNF complexes [53].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the hypoxanthine phosphoribosyltransferase gene on the inactive X chromosome is not transcribed, and its promoter is occupied by nucleosomes, and it is not DNase I hypersensitive. Reactivation of the inactive allele by azadeoxycytidine is accompanied by the appearance of hypoxanthine phosphoribosyltransferase mRNA and the DHS (54). Similarly, ␤-globin transcription is dependent upon the erythroid Krueppel-like factor (EKLF) transcription factor.…”
Section: Significance Of Dhss At P53-regulated Promoters Under Nonindmentioning
confidence: 99%